Enabling formulations of aprepitant: in vitro and in vivo comparison of nanocrystalline, amorphous and deep eutectic solvent based formulations - Henrik Palmelund; Jonas B. Eriksen; Annette Bauer-Brandl; Jukka Rantanen; Korbinian Löbmann (Elsevier, 2021)
A deep eutectic solvent (DES) is a eutectic system consisting of hydrogen bond donor and acceptor has been suggested as a promising formulation strategy for poorly soluble drugs. A DES consisting of choline chloride and levulinic acid in a 1:2  molar ratio was used to formulate a liquid solution of the model drug aprepitant. This formulation was tested in vitro (drug release and permeability) and in vivo (rat model) and compared with the performance of amorphous aprepitant and the commercial aprepitant nanocrystalline formulation. In this study a DES formulation is compared for the first time directly to other established enabling formulations. The in vitro drug release study demonstrated that the DES formulation and the amorphous form both were able to induce an apparent supersaturation followed by subsequent drug precipitation. To mitigate the risk of precipitation, HPMC was predissolved in the dissolution medium, which successfully reduced the degree of precipitation. In line with the results from the release study, an in vitro permeation study showed superior permeation of the drug from the DES formulation and from the amorphous form compared to the nanocrystalline formulation. However, the promising in vitro findings could not be directly translated into an increased in vivo performance in rats compared to the nanocrystalline formulation. Whilst the DES formulation (34 ± 4%) showed a higher oral bioavailability compared to amorphous aprepitant (20 ± 4%), it was on par with the oral bioavailability obtained from the nanocrystalline formulation (36 ± 2%).